Factors prompting clients’ dropout in microfinance institutions: A case of small enterprise development agency and presidential trust fund in Morogoro Municipality, Tanzania - Bea George, K.; Mosha Goodluck E; Dimoso, Provident J. (Rural Development Planning (IRDP), 2025)
Paper submitted to the @ Rural Planning Journal